2012
DOI: 10.1371/journal.pone.0036915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Fidelity in Home-Visiting Programs a Qualitative Analysis of 1058 Home Visit Case Notes from 105 Families

Abstract: ObjectiveImplementation fidelity is a key issue in home-visiting programs as it determines a program’s effectiveness in accomplishing its original goals. This paper seeks to evaluate fidelity in a 27-month program addressing maternal and child health which took place in France between 2006 and 2011.MethodTo evaluate implementation fidelity, home visit case notes were analyzed using thematic qualitative and computer-assisted linguistic analyses.ResultsDuring the prenatal period, home visitors focused on the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…However, health visitors carrying out home visits can be unsettled by the perceived gap between the theoretical content relating to intervention and the social situation of the families (19). In the present study, although a recently published analysis of home visit reports showed that the essential elements planned for the intervention were being delivered to the families in question, these reports also regularly underlined the distance between the attachmentfocused CAPEDP intervention and the pressing social, health and psychological needs of the families participating in the study (20). As Darius Tandon et al (19) and Saïas et al (20) have pointed out, home visitors trained to be health care providers can be unsettled by families' social and economic difficulties, questioning the idea of having a homogeneous team of home visitors in terms of their professional training.…”
Section: Discussionmentioning
confidence: 57%
“…However, health visitors carrying out home visits can be unsettled by the perceived gap between the theoretical content relating to intervention and the social situation of the families (19). In the present study, although a recently published analysis of home visit reports showed that the essential elements planned for the intervention were being delivered to the families in question, these reports also regularly underlined the distance between the attachmentfocused CAPEDP intervention and the pressing social, health and psychological needs of the families participating in the study (20). As Darius Tandon et al (19) and Saïas et al (20) have pointed out, home visitors trained to be health care providers can be unsettled by families' social and economic difficulties, questioning the idea of having a homogeneous team of home visitors in terms of their professional training.…”
Section: Discussionmentioning
confidence: 57%
“…This type of home‐visitor tailoring has been found in other home visiting programs besides Family Spirit (Donelan‐McCall, Eckenrode, & Olds, ) but has not been systematically studied. However, ad hoc tailoring of the standard model has also been found to decrease fidelity (Saias et al, ). There is a need for home visiting models to provide evidence‐informed flexibility to help guide home visitors in knowing when and how to adapt the intervention and ensure that all families are receiving what we know works (Rotheram‐Fuller et al, ; Saias et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Saıa T, Lerner E, Greacen T, Simon-Vernier E, Emer A, Pintaux E, Guedeney A, Dugravier R, Tereno S, Falissard B, Tubach F (2012) (23) To assess home visit fidelity through the notebooks of visits.…”
Section: Families (N= 07) United Statesmentioning
confidence: 99%